INTEGRATION PROCESSES IN UKRAINE AND THEIR INFLUENCE ON THE DEVELOPMENT OF INTERNATIONAL BUSINESS - Domashenko, Maryna; Musiienko, Oksana (Socio-economic relations in the digital society, 2023)
The topic of integration processes in Ukraine and their impact on the development of international business is important and relevant in the context of the country’s economic development. Ukraine’s integration with global economic structures, such as the European Union and other regional blocs, opens up new opportunities for international business and has a significant impact on the development of the country’s economy. The accession of Ukraine to the European Union and the signing of regional agreements contribute to the increase of trade relations and cooperation with other countries. This stimulates the growth of exports and the attraction of foreign investments, as well as promotes the transfer of best practices and technologies. International companies have the opportunity to expand their activities in the Ukrainian market and use its potential. However, integration also presents Ukrainian companies with challenges related to competition in the foreign market and the need to improve production processes and product quality. For the successful development of international business, it is important to attract foreign partners, introduce innovative technologies, improve the qualifications of employees and develop efficient logistics. Therefore, integration processes in Ukraine have a significant impact on the development of international business, create new opportunities for enterprises, and contribute to the attraction of foreign investments and the transfer of best practices. However, successful management of these processes requires effective strategies, adaptation to international standards and constant improvement of the competitiveness of Ukrainian business. The article examines integration processes in Ukraine and determines their impact on the development of international business; the challenges and opportunities of integration processes for the development of international business in Ukraine are considered.